The Contribution of Women in Religious Preaching in the Middle East - Arif, Abid Faturrahman; Nurwahidin, Nurwahidin (Publik : (Jurnal Ilmu Administrasi), 2024)
This article is based by the domination of the role of men over women in Middle Eastern society, whereas  when viewed from the religious perspective of the majority of Middle Eastern society, namely Islam, women  is highly respected and have a special position in society. This is due to the pre-Islamic culture and  perceptions that undermine women in their social status, so that women are only objects of entertainment,  household and sexuality without being permitted to massive public activities. This situation lasted for some  time, until finally a modern religious and social-based movement that fought for women's rights emerged.  According to the theory of liberal feminism, women should get the same rights as men, while maintaining the  natural differences that exist between the two. A woman cannot be confined at home and taking care of her  family, but she has the right to socialize and appear in public. Although discrimination against women  continues, in fact there are women who have recorded their role of preaching to society. If all this time the  preachers were generally male, then history records that there were female preachers who were influential in  the religious life of Middle Eastern society. The research method I use is descriptive-analysis based on  literature review. Based on the study that I convey in this article, the contribution of women in religious  preaching in the Middle East is a reality that should be appreciated amidst globalization and modernization,  even though the culture of patriarchy and women's subordination has not completely disappeared and has  become a hereditary culture of Middle Eastern society.